Efficacy of a Test-Retest Strategy in Residents and Health Care Personnel of a Nursing Home Facing a COVID-19 Outbreak - Blain, Hubert; Rolland, Yves; Tuaillon, Edouard; Giacosa, Nadia; Albrand, Mylène; Jaussent, Audrey; Benetos, Athanase; Miot, Stéphanie; Bousquet, Jean (Journal of the American Medical Directors Association, 2020)
To assess the American Testing Guidance for Nursing Homes (NHs)-updated May 19, 2020-with a new COVID-19 case. Case investigation. All 79 residents and 34 health care personnel (HCP) of an NH. Seven days after identification of a COVID-19 resident, all residents and HCP underwent real-time reverse-transcriptase polymerase chain reaction (rRT-PCR) testing for SARS-CoV-2 with nasopharyngeal swabs. This was repeated weekly in all previously negative subjects until the testing identified no new cases, and in all positive subjects until the testing was negative. COVID-19 infection prevention and control (IPC) measures were implemented in all residents and HCP with positive testing or with COVID-19 symptoms. Standard IPC was also implemented in all HCP. Six weeks after initial testing, all residents underwent testing for enzyme-linked immunosorbent assay-based IgG antibodies directed against the SARS-CoV-2. Symptoms were serially recorded in residents and HCP. A total of 36 residents had a positive rRT-PCR at baseline and 2 at day 7. Six HCP had a positive rRT-PCR at baseline and 2 at day 7. No new COVID-19 cases were diagnosed later. Among the SARS-CoV-2-positive cases, 6 residents (16%) and 3 HCP (37%) were asymptomatic during the 14 days before testing. Twenty-five residents (92.3%) and all 8 HCP (100%) with a positive rRT-PCR developed IgG antibodies against SARS-CoV-2. Among the residents and HCP always having tested negative, 2 (5%) and 5 (11.5%), respectively, developed IgG antibodies against SARS-CoV-2. These 2 residents had typical COVID-19 symptoms before and after testing and 2/5 HCP were asymptomatic before and after testing. This study shows the validity of the updated American Testing Guidance for Nursing Homes (NHs). It suggests implementing COVID-19 IPC in both residents and HCP with positive testing or COVID-19 symptoms and warns that asymptomatic HCP with repeated negative rRT-PCR testing can develop antibodies against SARS-CoV-2.